Unraveling Employee Performance: The Role of Human Resource Competency and Work Environment Through Job Satisfaction - Biveny Dyahpalupi; Siwi Dyah Ratnasari (Universitas KH. Abdul Chalim Mojokerto, 2026)
Human resource performance in public sector auditing institutions is influenced not only by technical competence but also by organizational conditions that shape employee satisfaction and productivity. However, empirical evidence regarding how competence and work environment interact with job satisfaction to influence auditor performance in regional government institutions remains limited. This study aims to examine the direct and indirect effects of human resource competence and work environment on the performance of civil servant auditors, with job satisfaction acting as a mediating variable. This research employed a quantitative explanatory design. Data were collected from 41 civil servant auditors working at the Regional Inspectorate of Malang Regency through a structured questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.0 to assess direct and mediating effects among the variables. The results indicate that human resource competence and work environment significantly influence job satisfaction. Human resource competence also demonstrates a significant positive effect on auditor performance. In contrast, the work environment does not show a direct significant relationship with performance. Mediation analysis reveals that job satisfaction significantly mediates the relationships between human resource competence and the work environment, on the one hand, and employee performance, on the other hand. These findings highlight the strategic role of competency development and job satisfaction in improving the performance of public sector auditors. Strengthening professional competencies, supported by a work environment that enhances job satisfaction, may serve as an effective organizational strategy to improve audit performance in government institutions. This study contributes to the literature on public sector human resource management by providing empirical evidence on the mediating role of job satisfaction in the relationship between competence, work environment, and auditor performance